2008
DOI: 10.1161/circulationaha.107.761031
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiac Myocyte Progenitors in Failing Human Hearts

Abstract: Background-Increasing evidence, derived mainly from animal models, supports the existence of endogenous cardiac renewal and repair mechanisms in adult mammalian hearts that could contribute to normal homeostasis and the responses to pathological insults. Methods and Results-Translating these results, we isolated small c-kit ϩ cells from 36 of 37 human hearts using primary cell isolation techniques and magnetic cell sorting techniques. The abundance of these cardiac progenitor cells was increased nearly 4-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 30 publications
7
72
2
Order By: Relevance
“…Other injectable biomaterials that complex HGF via affinity interactions with sulfated groups have shown a similar enhancement of function over delivery of the growth factor alone, both in hindlimb ischemia [26] and MI models [30]. The presentation of a supportive extracellular environment may also be important for cell infiltration post-MI; it has been shown that cardiac progenitor cells are present in higher numbers in failing human hearts, but the harsh environment prevents their positive contribution to repair [47]. Utilizing a biomaterials scaffold derived from ECM components may provide a new template for constructive remodeling, thereby facilitating cellular infiltration such as neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Other injectable biomaterials that complex HGF via affinity interactions with sulfated groups have shown a similar enhancement of function over delivery of the growth factor alone, both in hindlimb ischemia [26] and MI models [30]. The presentation of a supportive extracellular environment may also be important for cell infiltration post-MI; it has been shown that cardiac progenitor cells are present in higher numbers in failing human hearts, but the harsh environment prevents their positive contribution to repair [47]. Utilizing a biomaterials scaffold derived from ECM components may provide a new template for constructive remodeling, thereby facilitating cellular infiltration such as neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Being a circulating cell population, these CD133+ cells present an interesting cell pool that could be targeted to home to the site of injury and contribute to muscle repair. The ability of these cells to home and respond to injury has been reported in a number of studies, particularly in ischemic injury of the heart (Kania et al 2009;Kubo et al 2008;Voo et al 2008;Navarro-Sobrino et al 2010). Torrente et al (2004) have shown that the direct injection of CD133+ cells into dystrophic muscle improves skeletal muscle structure and replenishes the satellite cell pool, leading to a successful phase I clinical trial of autologous CD133+ cell injection in eight individuals with Duchenne muscular dystrophy .…”
Section: Recruitment Of Myogenic Progenitor Cellsmentioning
confidence: 97%
“…During development, c-kit is also expressed by immature endothelial cells and cardiomyocytes 42 . Small round cells expressing c-Kit have been identified in the perivascular compartment of the adult heart, and their abundance increases in human heart failure 43 . Following isolation from rat and human hearts, c-Kit+ cells have been reported to give rise to cardiomyocytes, smooth muscle cells and endothelial cells.…”
Section: Stem Cells and Cell Therapymentioning
confidence: 99%